Knowledge Spillovers and Economic Growth - André van Stel; Henry Nieuwenhuijsen (Tinbergen Institute, 2002)
The importance of knowledge spillovers for achieving innovation and economic growth is widely recognized. It is not straightforward which type of spillovers is most effective: intra-sectoral spillovers or inter-sectoral spillovers. We investigate this controversy using a model of regional growth. The model also deals with the impact of local competition on innovation and growth. The model is estimated using sectoral data for 40 Dutch regions in the period 1987-1995. We find that local competition is important particularly for economic growth in industry sectors (manufacturing and construction), while diversity, a proxy for inter-sectoral spillovers, is important particularly for growth in service sectors. We find no effect for specialization (a proxy for intra-sectoral spillovers).
Keywords: O31; R11; 330; knowledge spillovers; innovation; economic growth; industry structure; Wissenstransfer; Imitationsstrategie; Regionales Wachstum; Interindustrielle Verflechtung; Regionale Arbeitsteilung; Niederlande